2004
DOI: 10.4314/eamj.v81i7.9191
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellae carrier status of food vendors in Kumasi, Ghana

Abstract: Objective: To determine the prevalence of chronic typhoidal salmonellae amongst food vendors in Kumasi Ghana. Design: A prospective study. Setting: Sitting and itinerant food vendors in Kumasi. Methods: Screening of 258 (230 females of 28 males) healthy food vendors for Salmonella typhi, and S. paratyphi A, B, and C, using stool culture, the widal test, and standard microbiological identification methods. Main outcome measures: Prevalence of chronic typhoidal Salmonellae carriers among food vendors in Kumasi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 3 publications
7
46
2
Order By: Relevance
“…In Irbid, Jordan [3], out of 283 food-handlers screened, 17 (6%) were Salmonella carriers. In Ghana [12], 258 asymptomatic food vendors were screened and Salmonella was isolated from 6 (2.3%). In India [5], among 35 individuals screened 6 (17.14%) were positive for Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…In Irbid, Jordan [3], out of 283 food-handlers screened, 17 (6%) were Salmonella carriers. In Ghana [12], 258 asymptomatic food vendors were screened and Salmonella was isolated from 6 (2.3%). In India [5], among 35 individuals screened 6 (17.14%) were positive for Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Yismaw G et al reported that 79.2% and 44.1%of S. typhi isolated from clinical samples in Gondar University hospital were resistant to chloramphenicol and gentamicine respectively (9). Studies had demonstrated that food handlers harbour S. typhi asymptomatically (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…One article in our study reported that food handlers constitute a significant risk in the spread of enteric fever in Kumasi [18]. This observation calls for concern because the situation could be worse in other towns where food safety education is generally lacking.…”
Section: Discussionmentioning
confidence: 73%
“…The selected articles came from the following journals: three from Acta Tropica [11][12][13], two from the Ghana Medical Journal [14,15], two from the International Journal of Microbiology [16,17], and one each from the East African Medical Journal [18], the Journal of Urban Health [19], Archives of Environmental Contamination and Toxicology [20], and the Bulletin of the World Health Organization [21]. Published studies on food safety were observed to have mainly been based on research performed in the southern half of the country, with the majority of publications coming from the capital Accra and its environs ( Figure 1).…”
Section: Source and Geographical Distribution Of Articlesmentioning
confidence: 99%